Disgust, Moral Disgust, and Morality - Gert, Joshua (Journal of moral philosophy, 2015)
This paper calls into question the idea that moral disgust is usefully regarded as a form of genuine disgust. This hypothesis is questionable even if, as some have argued, the spread of moral norms through a community makes use of signaling mechanisms that are central to core disgust. The signaling system is just one part of disgust, and may well be completely separable from it. Moreover, there is plausibly a significant difference between the cognitive scientist’s concept of an emotion and the everyday notion of that emotion. Finally, even if, as this paper contests, some form of disgust were directly elicited by the moral wrongness of certain kinds of behavior, research on the socio-moral elicitors of the disgust mechanism would still be unlikely to shed much direct light on the nature or content of morality.